Enhancing Science Process Skills and Self-Regulation: Is It Better To Use Inquiry Interactive Demonstration Model? - Kurniawan, Fauzan; Djukri, Djukri (Jurnal Pendidikan Progresif, 2022)
Enhancing Science Process Skills and Self-Regulation: Is It Better To Use Inquiry Interactive Demonstration Model?. Objectives: This study aims to find out the effectiveness of the inquiry interactive demonstration model to improve students' science process skills and self-regulation. Methods:  This study used a Quasy Experiment, and research design of The Matching Only Pretest-Posttest Design. This study's population was all 8th-grade students of Junior High School 19 of Bandar Lampung, Lampung, Indonesia, and used a sample of 60 students. The data were analyzed with descriptive statistics with Multivariate statistical test (Mannova test). Findings: The result of the Multivariate statistical test of the students’ science process skills was Sig. = 0.000, p<0.05). Meanwhile, The result of the Multivariate statistical test of the students’ self-regulation was Sig. = 0.000, p<0.05). Conclusion: The inquiry interactive demonstration learning model can improve science process skills and self-regulation. Keywords: inquiry interactive demonstration model, science process skills, self-regulation.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202238